Determination of diffusion coefficients and activation energy of selected organic liquids using reversed-flow gas chromatographic technique - Khalisanni Khalid,; Rashid Atta Khan,; Sharifuddin Mohd Zain, (Universiti Kebangsaan Malaysia, 2012)
Evaporation of vaporize organic liquid has ecological consequences when the compounds are introduced into both freshwater and marine environments through industrial effluents, or introduced directly into the air from industrial unit processes such as bioreactors and cooling towers. In such cases, a rapid and simple method are needed to measure physicochemical properties of the organic liquids. The Reversed-Flow Gas Chromatography (RF-GC) sampling technique is an easy, fast and accurate procedure. It was used to measure the diffusion coefficients of vapors from liquid into a carrier gas and at the same time to determine the rate coefficients for the evaporation of the respective liquid. The mathematical expression describing the elution curves of the samples peaks was derived and used to calculate the respective parameters for the selected liquid pollutants selected such as methanol, ethanol, 1-propanol, 1-butanol, n-pentane, n-hexane, n-heptane and n-hexadecane, evaporating into the carrier gas of nitrogen. The values of diffusion coefficients found were compared with those calculated theoretically or reported in the literature. The values of evaporation rate were used to determine the activation energy of respective samples using Arrhenius equation. An interesting finding of this work is by using an alternative mathematical analysis based on equilibrium at the liquid-gas interphase, the comparison leads to profound agreement between theoretical values of diffusion coefficients and experimental evidence.